Kemanusiaan Yesus Kristus - Tamyong, Rospianti (JURNAL ILUMINASI, 2023)
Jesus truly appeared as a human being in the following realities: According to the genealogy, Jesus' ancestors were traced back to Abraham (Matt 1:1-17). Jesus was born to his mother Mary, being male, wrapped in swaddling clothes and laid in a manger (Luke 2:1-7). He worked as a carpenter (Mark 6:3), could become angry (Luke 19:45), experience sadness (14:34), feel hungry (Matt 21:18), thirst (Matt 25:35), fear (Mark 22:44). The humanity of Jesus becomes profoundly evident when he had to undergo the fate experienced by all human beings, namely death (Luke 23:44-49, Mark 15:33-41, Matt 27:45-56, John 19:28-30). These various events aim to affirm that Jesus lived within human history and lived a life like that of ordinary human beings.